Restoring grassy woodland diversity through direct seeding: Insights from six 'best‐practice' case studies in southern Australia. (May 2018) - Cuneo, Peter; Gibson‐Roy, Paul; Fifield, Graham; Broadhurst, Linda; Berryman, Tim; Crawford, Andrew; Freudenberger, David
Abstract : Ecological restoration of grassy woodland ecosystems is now a significant landscape‐scale conservation objective throughout southern Australia. Technological improvements in direct seeding are now sufficiently well‐advanced to examine whether cost‐effective restoration of grassy woodlands is feasible. Consideration of six 'best practice case studies shows substantial evidence of success. Further refinement of direct seeding techniques, in combination with native seed production systems, however, will be required into the future to meet the scale of woodland conservation targets and restore ecological function.